Method for manufacturing a cylindrical honeycomb structure filter
Patent Information
- Application Number
- CN202310047638.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-04
- Filing Date
- 2020-12-18
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2040-12-18
AI Technical Summary
[0045]本发明的一个实施方式所涉及的柱状蜂窝结构过滤器能够有助于兼具PN高捕集效率及低压力损失。
Smart Images

Figure CN116078067B_ABST
Abstract
Description
[0001] This application is a divisional application of the invention patent application with application number 202011500270.0, application date December 18, 2020, entitled "Columnar honeycomb structure filter and manufacturing method thereof". Technical Field
[0002] This invention relates to columnar honeycomb structure filters and their manufacturing methods. Background Technology
[0003] Exhaust gases from internal combustion engines such as diesel and gasoline engines contain particulate matter (PM). PM is harmful to human health, and its emission is restricted. Currently, to address these emissions restrictions, filters such as DPF and GPF are widely used, which filter PM by passing exhaust gases through permeable pores.
[0004] As a filter for capturing PM, a wall-flow columnar honeycomb structure (hereinafter also referred to as a "columnar honeycomb structure filter") is known, which has a plurality of first compartments and a plurality of second compartments, wherein the plurality of first compartments extend from the bottom surface of the inlet side to the bottom surface of the outlet side in the height direction, and the bottom surface of the inlet side is open and the bottom surface of the outlet side has a sealing portion, and the plurality of second compartments are arranged adjacent to the first compartments in a manner that sandwiches the partition wall, extend from the bottom surface of the inlet side to the bottom surface of the outlet side in the height direction, and the bottom surface of the inlet side has a sealing portion and the bottom surface of the outlet side is open.
[0005] In recent years, with the strengthening of exhaust gas restrictions, stricter PM emission standards (PN limit: Particle Matter number limit) have been introduced, requiring filters to have high PM capture performance (high PN capture efficiency). Therefore, it has been proposed to form an additional layer for PM capture on the surface of the compartment.
[0006] Patent Document 1 discloses a method for manufacturing a honeycomb filter for dust collection, which involves forming at least one porous membrane with a pore size smaller than that of the porous substrate on the surface of a honeycomb porous substrate. The method is characterized in that a membrane with a particle size of 50% (D...) is supplied into the compartments of the porous substrate. 50 A slurry is prepared by aggregate particles whose average pore diameter (P: μm) is more than 2 / 3 times but less than 1 times that of the porous substrate and whose particle size distribution is within the range of the following formula (1). The water in the slurry is removed through the pores of the porous substrate, thereby forming a film. Then, firing is performed.
[0007] D 50 / (D 50 -D 10)≥1.5 … (1)
[0008] (where D) 50 50% particle size (μm), D 10 10% of the particle size (μm)
[0009] Furthermore, Patent Document 1 describes a honeycomb filter for dust collection, wherein at least one porous membrane with a pore size smaller than that of the porous substrate is formed on the surface of a honeycomb porous substrate. The honeycomb filter for dust collection is characterized in that the first porous membrane layer consists of 50% particles with a diameter (D) of 50% or less than that of the porous substrate. 50 The aggregate particles are composed of aggregate particles whose average pore size (P: μm) is more than 2 / 3 times but less than 1 times that of the average pore size (P: μm) of the porous substrate and whose particle size distribution is within the range of the following formula (1), and whose average film thickness is more than 3 times that of the 50% particle size.
[0010] D 50 / (D 50 -D 10 )≥1.5 … (1)
[0011] (where D) 50 50% particle size (μm), D 10 10% of the particle size (μm)
[0012] According to Patent Document 1, by using a slurry prepared from aggregate particles with an average particle size and particle size distribution within a specified range to form a film, a honeycomb filter with high capture efficiency and low pressure loss can be easily manufactured with a simple device, and a large number of filters can be manufactured with uniform quality.
[0013] Patent document 2 describes a method for manufacturing a multilayer honeycomb filter, wherein a slurry of ceramic particles with an average particle size of more than 2 / 3 times but less than 1 times the average pore size of the substrate is supplied to each compartment of a substrate having a honeycomb structure, and the water in the slurry is removed by passing through the pores of the substrate, thereby causing the ceramic particles to adhere to the surface of the substrate. Next, firing is performed, thereby forming a coating on the surface of the substrate.
[0014] In addition, Patent Document 2 describes a multi-layer honeycomb filter, which is a multi-layer honeycomb filter for dust collection with one or more coatings formed by ceramic particles with an average particle size different from that of the ceramic particles constituting the substrate on the surface of a substrate having a honeycomb structure. The multi-layer honeycomb filter for dust collection is characterized in that the average particle size of the coating in contact with the substrate is more than 2 / 3 times but less than 1 times the average pore size of the substrate, and the average thickness of the coating in contact with the substrate is less than 7 times the average particle size of the coating.
[0015] According to Patent Document 2, the multi-layer honeycomb filter has high capture efficiency, low pressure loss, and low pressure loss rise rate.
[0016] Patent Document 3 describes the formation of a porous layer with a porosity of 90% or more and an average thickness of 0.5 μm to 30 μm. Patent Document 3 also describes how the high porosity of the porous layer can eliminate the impact of pressure loss on the honeycomb structure.
[0017] Existing technical documents
[0018] Patent documents
[0019] Patent Document 1: Japanese Patent Application Publication No. 2001-79321
[0020] Patent Document 2: Japanese Patent Application Publication No. 2000-202220
[0021] Patent Document 3: International Publication No. 2019 / 089806 Summary of the Invention
[0022] In terms of the high PM capture efficiency and low pressure loss of columnar honeycomb structure filters, forming a layer on the surface of the compartment for PM capture is considered effective. However, there is room for improvement in this layer. If the layer is improved from a different perspective than before, the technical options increase. In addition, it is also advantageous from the perspective of expanding the possibility of future research and development.
[0023] Therefore, in one embodiment of the present invention, the objective is to provide a columnar honeycomb structure filter that, based on a different perspective than previously thought, facilitates both high PN capture efficiency and low pressure loss. Furthermore, in another embodiment of the present invention, the objective is to provide a method for manufacturing the aforementioned columnar honeycomb structure filter.
[0024] The inventors of this invention conducted in-depth research to solve the aforementioned problems and discovered that, regarding the layer on the surface of the compartment used for PM capture (referred to as a "porous membrane" in this invention), satisfying a specified relationship between the average membrane thickness and porosity is effective in maintaining low pressure loss and improving PM capture efficiency. This invention is based on this insight, as illustrated below.
[0025] [1] A columnar honeycomb structure filter comprising: a plurality of first compartments extending from an inlet-side bottom surface to an outlet-side bottom surface, wherein the inlet-side bottom surface is open and the outlet-side bottom surface has a sealing portion; and a plurality of second compartments extending from an inlet-side bottom surface to an outlet-side bottom surface, wherein the plurality of first compartments and the plurality of second compartments are alternately arranged adjacent to each other with porous partition walls.
[0026] The columnar honeycomb structure filter is characterized in that...
[0027] A porous ceramic membrane is formed on the surface of each first compartment. The average membrane thickness T (unit: μm) of the porous membrane is 2 to 50 μm, and the porosity P (unit: %) is 65 to 90%. The average membrane thickness T and porosity P satisfy the relationship 0.36T+60≤P≤0.75T+72.
[0028] [2] The columnar honeycomb structure filter according to [1] is characterized in that,
[0029] The average membrane thickness T (unit: μm) of the porous membrane is 2–40 μm, and the porosity P (unit: %) is 65–90%.
[0030] [3] The columnar honeycomb structure filter according to [1] or [2] is characterized in that,
[0031] The porous membrane contains a total of more than 50% by mass of one or more of silicon carbide, cordierite, alumina, silica, andalusite and aluminum titanate.
[0032] [4] The columnar honeycomb structure filter according to any one of [1] to [3] is characterized in that,
[0033] The porous septum contains more than 50% cordierite by mass.
[0034] [5] A method for manufacturing a columnar honeycomb structure filter, comprising the following steps:
[0035] A process for preparing a columnar honeycomb structure, the columnar honeycomb structure comprising: a plurality of first compartments extending from the bottom surface of the inlet side to the bottom surface of the outlet side, the bottom surface of the inlet side being open and the bottom surface of the outlet side having a sealing portion; and a plurality of second compartments extending from the bottom surface of the inlet side to the bottom surface of the outlet side, the bottom surface of the inlet side having a sealing portion and the bottom surface of the outlet side being open, the plurality of first compartments and the plurality of second compartments being arranged alternately adjacent to each other with porous partition walls between them;
[0036] In the process of simultaneously spraying an aerosol containing ceramic particles toward the bottom surface of the inlet side and applying an attractive force to the bottom surface of the outlet side to draw the sprayed aerosol from the bottom surface of the inlet side, thereby adhering the ceramic particles to the surface of the first compartment, the ceramic particles satisfy the following conditions when the median particle size in the cumulative particle size distribution based on volume diffraction scattering determined by laser diffraction scattering is set as D50 (unit: μm), the 10% particle size is set as D10 (unit: μm), and the 90% particle size is set as D90 (unit: μm): 0.1 ≤ D50 ≤ 6.0 and 0.4 ≤ D50 / (D90-D10); and
[0037] The process involves heat-treating a columnar honeycomb structure with ceramic particles attached to the surface of the first compartment at a maximum temperature of 1000°C or higher for more than 1 hour to form a porous membrane on the surface of the first compartment with an average film thickness T and D50 satisfying the relationship 4×D50≤T≤20×D50.
[0038] [6] The method for manufacturing a columnar honeycomb structure filter according to [5] is characterized in that,
[0039] The porous membrane contains a total of more than 50% by mass of one or more of silicon carbide, cordierite, alumina, silica, andalusite and aluminum titanate.
[0040] [7] The method for manufacturing a columnar honeycomb structure filter according to [5] or [6] is characterized in that,
[0041] The porous septum contains more than 50% cordierite by mass.
[0042] [8] A method for manufacturing a columnar honeycomb structure filter according to any one of [5] to [7], characterized in that,
[0043] The average thickness of the porous membrane is 2–50 μm.
[0044] Invention Effects
[0045] One embodiment of the present invention relates to a columnar honeycomb structure filter that can help achieve both high PN capture efficiency and low pressure loss. Attached Figure Description
[0046] Figure 1 This is a perspective view schematically illustrating an example of a columnar honeycomb structure filter.
[0047] Figure 2 This is a schematic cross-sectional view of an example of a columnar honeycomb structure filter, viewed from a section parallel to the direction of the compartment extension.
[0048] Figure 3 This is a schematic, enlarged view of a columnar honeycomb filter when viewed from a cross-section orthogonal to the direction of the compartment extension.
[0049] Figure 4 This is a schematic diagram of the cross-section of a columnar honeycomb filter cut out to determine the average thickness of the porous membrane.
[0050] Figure 5 This is a schematic diagram illustrating the configuration of a particle attachment device according to one embodiment of the present invention.
[0051] Figure 6This is a graph showing the relationship between the average membrane thickness and porosity of the porous membranes in the embodiments and comparative examples.
[0052] Figure 7 This is a graph showing the relationship between the median particle size (D50) of ceramic particles in the aerosol in the examples and comparative examples and the average thickness of the porous membrane.
[0053] Figure 8 This is an example of an FE-SEM image of the porous membrane in Example 2.
[0054] Symbol Explanation
[0055] 100…Columnar honeycomb structure filter, 102…Outer peripheral sidewall, 104…Inlet side bottom surface, 106…Outlet side bottom surface, 108…First compartment, 109…Sealing part, 110…Second compartment, 112…Partition wall, 114…Porous membrane, 500…Particle attachment device, 510…Aerosol generator, 511…Nozzle, 512…Ceramic particles, 513…Cylinder, 513e…Cylinder outlet, 514…Piston or screw, 515…Crushing chamber, 515e…Crushing chamber outlet, 516…Rotating body, 517…Gas flow path, 520…Laser diffraction particle size distribution measuring device, 530…Gas inlet pipe, 531…Ventilation hole, 540…Holding element, 550…Differential pressure gauge, 560…Exhaust pipe, 570…Blower, 580…Columnar honeycomb structure. Detailed Implementation
[0056] Next, embodiments of the present invention will be described in detail with reference to the accompanying drawings. The present invention is not limited to the following embodiments, and it should be understood that appropriate design changes, modifications, etc., can be made based on ordinary knowledge of those skilled in the art without departing from the spirit of the present invention.
[0057] <1. Columnar honeycomb structure filter>
[0058] A columnar honeycomb structure filter according to one embodiment of the present invention will be described. The columnar honeycomb structure filter can be used as a DPF (Diesel Particulate Filter) or GPF (Gasoline Particulate Filter) for collecting soot, typically mounted on the exhaust line of a combustion device, such as an engine mounted in a vehicle. The columnar honeycomb structure filter according to the present invention can, for example, be installed inside an exhaust pipe.
[0059] Figure 1 and Figure 2The diagram illustrates a schematic perspective view and a cross-sectional view of a columnar honeycomb structure filter (100). The columnar honeycomb structure filter (100) includes: an outer peripheral sidewall (102); a plurality of first compartments (108) disposed on the inner peripheral side of the outer peripheral sidewall (102), extending from the bottom surface of the inlet side (104) to the bottom surface of the outlet side (106), wherein the bottom surface of the inlet side (104) is open and the bottom surface of the outlet side (106) has a sealing portion (109); and a plurality of second compartments (110) disposed on the inner peripheral side of the outer peripheral sidewall (102), extending from the bottom surface of the inlet side (104) to the bottom surface of the outlet side (106), wherein the bottom surface of the inlet side (104) has a sealing portion (109) and the bottom surface of the outlet side (106) is open. In the columnar honeycomb structure (100), the first compartment (108) and the second compartment (110) are arranged alternately adjacent to each other with porous partitions (112), so that the bottom surface of the inlet side (104) and the bottom surface of the outlet side (106) respectively present a honeycomb shape.
[0060] When exhaust gas containing particulate matter (PM) such as soot is supplied to the inlet-side bottom surface (104) on the upstream side of the columnar honeycomb structure filter (100), the exhaust gas is introduced into the first compartment (108) and proceeds downstream within the first compartment (108). Since the first compartment (108) has a sealing portion (109) on the outlet-side bottom surface (106) on the downstream side, the exhaust gas flows into the second compartment (110) through the porous partition wall (112) that divides the first compartment (108) and the second compartment (110). The particulate matter cannot pass through the partition wall (112), and therefore is captured and accumulated in the first compartment (108). After the particulate matter is removed, the clean exhaust gas flowing into the second compartment (110) proceeds downstream within the second compartment (110) and flows out from the outlet-side bottom surface (106) on the downstream side.
[0061] Figure 3 The diagram shows a schematic, partially enlarged view of the columnar honeycomb filter (100) viewed in a cross section orthogonal to the direction in which the compartments (108, 110) extend. A porous ceramic membrane (114) is formed on the surface of each first compartment (108) of the columnar honeycomb filter (100) (the same surface as the partition wall (112) that divides the first compartment (108).
[0062] The porous membrane may contain one or more ceramics selected from silicon carbide (SiC), cordierite, talc, mica, andalusite, ceramic fragments, aluminum titanate, alumina, silicon nitride, silicon aluminum oxynitride ceramics, zirconium phosphate, zirconium oxide, titanium dioxide, and silicon dioxide (SiO2). For reasons of cost, availability, thermal shock resistance, and peel resistance, the porous membrane preferably contains a total of 50% by mass or more of one or more of silicon carbide, cordierite, alumina, silicon dioxide, andalusite, more preferably 70% by mass or more, and even more preferably 90% by mass or more. For reasons of peel resistance, the porous membrane particularly preferably contains 50% by mass or more of silicon carbide, more preferably 70% by mass or more, and even more preferably 90% by mass or more.
[0063] In one embodiment, the average thickness of the porous membrane is 2 to 50 μm. Having an average membrane thickness of 2 μm or more, preferably 3 μm or more, provides the advantage of improved capture efficiency. Furthermore, having an average membrane thickness of 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less, provides the advantage of suppressing pressure loss increases.
[0064] In this specification, the average membrane thickness of the porous membrane in the columnar honeycomb structure filter is determined in the following order. The direction of the extension of the first compartment of the columnar honeycomb structure filter is set as the direction of the coordinate axis extension, the coordinate value of the bottom surface on the inlet side is set to 0, and the coordinate value of the bottom surface on the outlet side is set to X. Furthermore, the average thickness of the porous membrane is measured at each of the following 6 locations (A1, A2, A3, B1, B2, B3) with 5 fields of view, and the overall average value is taken as the average membrane thickness of the porous membrane of the columnar honeycomb structure.
[0065] A1: The center of the cross section of the columnar honeycomb structure filter within the coordinate range of 0.1X to 0.3X, orthogonal to the direction of extension of the first compartment.
[0066] B1: The outer periphery of the cross section of the columnar honeycomb structure filter in the coordinate range of 0.1X to 0.3X, which is orthogonal to the direction of extension of the first compartment.
[0067] A2: The center of the cross section of the columnar honeycomb structure filter in the coordinate range of 0.4X to 0.6X, which is orthogonal to the direction of extension of the first compartment.
[0068] B2: The outer periphery of the cross section of the columnar honeycomb structure filter in the coordinate range of 0.4X to 0.6X, which is orthogonal to the direction of extension of the first compartment.
[0069] A3: The center of the cross section of the columnar honeycomb structure filter in the coordinate range of 0.7X to 0.9X, which is orthogonal to the direction of extension of the first compartment.
[0070] B3: The outer periphery of the cross section of the columnar honeycomb structure filter in the coordinate range of 0.7X to 0.9X, which is orthogonal to the direction of extension of the first compartment.
[0071] The following describes how the central and peripheral portions of a columnar honeycomb filter are determined when measuring the average thickness of the porous membrane. When observing the columnar honeycomb filter from a cross-section orthogonal to the direction extending from the first compartment, a line segment is drawn from the centroid of this cross-section toward the outer surface of the peripheral sidewall. The direction in which this line segment extends is defined as the direction of the coordinate axis extension. The coordinate value of the centroid is set to 0, and the coordinate value of the outer surface of the peripheral sidewall is set to R. In this case, the range of coordinate values 0 to 0.2R on this line segment represents the central portion, and the range of coordinate values 0.7R to 0.9R represents the peripheral portion. By drawing multiple such line segments in this cross-section and combining the central and peripheral portions of each line segment, the range of the central and peripheral portions in this cross-section is obtained.
[0072] The average thickness of the porous membrane at various points A1, A2, A3, B1, B2, and B3 was determined using the following method. A cross-section was cut from the columnar honeycomb filter at the location (center or periphery) where the average thickness of the porous membrane was desired. This cross-section was parallel to the direction of extension of the first compartment and parallel to a line segment extending from the outer surface of the outer peripheral sidewall towards the center of gravity. The cross-section was observed using a 3D shape measuring machine (e.g., Keyence VR-3200) at 25x magnification and a viewing field of 12.5 mm (horizontal) × 9.5 mm (vertical). The observation was performed with the transverse direction of the viewing field parallel to the direction of extension of the first compartment.
[0073] Figure 4A schematic diagram of the cut cross-section is shown. By observing the cross-section, a first compartment (108) with a porous membrane and a second compartment (110) without a porous membrane are identified. Next, three adjacent first compartments (108) at their closest points on this cross-section are identified. Furthermore, the central region (110a) (reference plane) of the two second compartments (110) sandwiched by the three adjacent first compartments (108) at their closest points on this cross-section is identified. The reference plane is leveled using image processing software (e.g., the software included with the Keyence VR-3200 3D shape measuring machine) so that the reference plane is as horizontal as possible when viewed from the contours of the two regions. After leveling, the range of the central region (110a) of the two second compartments (110) is defined, and the average height H2 of this region is measured. Additionally, after leveling, the range of the central region (108a) of the three first compartments (108) is defined, and the average height H1 of this region is measured. The difference between the average height H1 and the average height H2 in a field of view is taken as the average thickness of the porous membrane in that field of view. It should be noted that the central region (108a, 110a) refers to the region in the center when the distance between the pair of partitions (112) that divide the area into compartments is trisected.
[0074] At each of A1, A2, A3, B1, B2, and B3, calculate the average thickness of the porous membrane at any five fields of view, and use these average thicknesses as the average thickness of the porous membrane at each of A1, A2, A3, B1, B2, and B3. Furthermore, take the overall average value as the average membrane thickness of the porous membrane in the columnar honeycomb filter.
[0075] In one embodiment, the porosity of the porous membrane is 65-90%. Combining this with the average membrane thickness of the porous membrane described above and controlling the porosity within this range is effective for achieving both high PN capture efficiency and low pressure loss. From the viewpoint of suppressing pressure loss increase, the porosity of the porous membrane is preferably 65% or more, more preferably 68% or more. Furthermore, from the viewpoint of obtaining high PN capture efficiency, the porosity of the porous membrane is preferably 90% or less, more preferably 85% or less, and even more preferably 80% or less.
[0076] For the porosity of the porous membrane, an Inlens backscattered electron image was captured from any two fields of view of the central region (108a) of the first compartment (108) where the porous membrane is formed, using a field emission scanning electron microscope (FE-SEM) (e.g., ZEISS ULTRA55). This image was taken from sections where the average membrane thickness at locations A1, A2, A3, B1, B2, and B3 was determined. Next, the image was binarized using image analysis software (e.g., HALCON) and divided into membrane and void portions. The ratio of the membrane portion to the void portion was calculated and set as the porosity of the porous membrane at locations A1, A2, A3, B1, B2, and B3. The overall average value of these values was then used as the porosity of the porous membrane of the columnar honeycomb filter.
[0077] In order to achieve both high PN capture efficiency and low pressure loss, for porous membranes, in addition to controlling the average membrane thickness and porosity within the above-mentioned ranges, the average membrane thickness T (unit: μm) and porosity P (unit: %) preferably satisfy the relationship 0.36T+60≤P≤0.75T+72, and more preferably satisfy the relationship 0.42T+67≤P≤0.75T+68.
[0078] The materials used to construct the porous partitions and outer peripheral sidewalls of the columnar honeycomb structure filter according to this embodiment are not limited, and porous ceramics can be cited as examples. Examples of ceramics include: cordierite, andalusite, zirconium phosphate, aluminum titanate, silicon carbide (SiC), silicon-silicon carbide composites (e.g., Si-bonded SiC), cordierite-silicon carbide composites, zircon, zirconium oxide, spinel, sapphire, pseudosapphire, corundum, titanium dioxide, silicon nitride, etc. These ceramics may contain only one type or two or more types simultaneously. In applications such as DPF and GPF filters, cordierite is preferably used as the ceramic. Therefore, the porous partitions and outer peripheral sidewalls preferably contain 50% by mass or more cordierite, more preferably 70% by mass or more, and even more preferably 90% by mass or more.
[0079] Columnar honeycomb filters sometimes carry PM combustion catalysts that assist in the combustion of PM such as soot, oxidation catalysts (DOC), SCR and NSR catalysts for removing nitrogen oxides (NOx), and three-way catalysts capable of simultaneously removing hydrocarbons (HC), carbon monoxide (CO), and nitrogen oxides (NOx). However, the columnar honeycomb filter according to this embodiment preferably does not carry a catalyst. This is because it would lead to an increase in pressure loss.
[0080] There are no restrictions on the bottom shape of the columnar honeycomb structure filter. For example, it can be circular, elliptical, racetrack-shaped, oblong, or other arc shapes, as well as polygonal shapes such as triangles and quadrilaterals. Figure 1 The bottom surface of the columnar honeycomb structure (100) is circular, and the whole structure is cylindrical.
[0081] The shape of the compartments in the cross-section perpendicular to the flow direction of the compartments is not limited, but quadrilaterals, hexagons, octagons, or combinations of these shapes are preferred. Among them, squares and hexagons are preferred. By making the compartments into the above shapes, the pressure loss when the fluid flows through the columnar honeycomb structure can be reduced.
[0082] Regarding the average pore size of the partition wall, it is preferably 20 μm or less, more preferably 18 μm or less, and even more preferably 16 μm or less. With an average pore size within this range, the collection efficiency of particulate matter is significantly improved. Furthermore, the average pore size of the partition wall is preferably 4 μm or more, more preferably 6 μm or more, and even more preferably 8 μm or more. With an average pore size within this range, pressure loss reduction can be suppressed. The average pore size of the partition wall refers to the value measured according to JIS-R1655:2003 using a mercury porosimeter.
[0083] From the viewpoint of suppressing the pressure loss of exhaust gas to a low level, the porosity of the partition wall is preferably 40% or more, more preferably 45% or more, and even more preferably 50% or more. Furthermore, from the viewpoint of ensuring the strength of the columnar honeycomb structure filter, the porosity of the partition wall is preferably 80% or less, more preferably 75% or less, and even more preferably 70% or less. The porosity of the partition wall refers to the value measured according to JIS-R1655:2003 using a mercury porosimeter.
[0084] From the viewpoint of suppressing pressure loss, the upper limit of the average thickness of the partition walls in the columnar honeycomb structure filter is preferably 0.59 mm or less, more preferably 0.33 mm or less, and even more preferably 0.26 mm or less. However, from the viewpoint of ensuring the strength of the columnar honeycomb structure filter, the lower limit of the average thickness of the partition walls is preferably 0.15 mm or more, more preferably 0.16 mm or more, and even more preferably 0.18 mm or more. In this specification, the thickness of the partition wall refers to the length of the line segment that traverses the partition wall when the centroids of adjacent compartments are connected by a line segment in a cross section orthogonal to the flow path of the compartment. The average thickness of the partition walls refers to the average value of the thicknesses of all partition walls.
[0085] There is no particular limitation on the compartment density (the number of compartments per unit cross-sectional area perpendicular to the direction of compartment extension), for example, it can be 6 to 2000 compartments / square inch (0.9 to 311 compartments / cm²). 2More preferably, it is 50–1000 compartments / square inch (7.8–155 compartments / cm²). 2 ), particularly preferred is 100–400 compartments / square inch (15.5–62.0 compartments / cm²). 2 ).
[0086] The columnar honeycomb filter can also be provided as a single-piece molded product. Alternatively, for the columnar honeycomb filter, multiple filter units, each with its own outer peripheral sidewall, can be integrally joined together sideways, providing a unit-jointed assembly. By providing the columnar honeycomb filter as a unit-jointed assembly, thermal shock resistance can be improved.
[0087] <2. Manufacturing method of columnar honeycomb structure filter>
[0088] The following is an illustrative description of a method for manufacturing a columnar honeycomb structure filter. First, a raw material composition containing ceramic raw materials, a dispersion medium, a pore-forming material, and a binder is mixed to form a blank. The blank is then extruded to form the desired columnar honeycomb structure. Additives such as dispersants may be added to the raw material composition as needed. During extrusion molding, a die with the desired overall shape, compartment shape, compartment wall thickness, and compartment density can be used.
[0089] After drying the columnar honeycomb molded body, sealing portions are formed at specified positions on both bottom surfaces of the columnar honeycomb molded body. Then, the sealing portions are dried to obtain a columnar honeycomb molded body with sealing portions. Subsequently, the columnar honeycomb molded body is degreased and fired to produce a columnar honeycomb structure.
[0090] As ceramic raw materials, materials capable of forming the aforementioned ceramics after firing can be used. Ceramic raw materials can be provided, for example, in powder form. Examples of ceramic raw materials include those used to obtain ceramics such as cordierite, andalusite, zirconium phosphate, aluminum titanate, silicon carbide (SiC), silicon-silicon carbide composites (e.g., Si-bonded SiC), cordierite-silicon carbide composites, zircon, zirconium oxide, spinel, Indian quartz, pseudosapphire, corundum, titanium dioxide, and silicon nitride. Specifically, without limitation, examples include: silicon dioxide, talc, alumina, kaolin, serpentine, pyrophyllite, brucite, boehmite, andalusite, magnesite, and aluminum hydroxide. One type of ceramic raw material can be used alone, or two or more can be used in combination.
[0091] In applications such as DPF and GPF filters, cordierite is preferred as the ceramic material. In this case, cordierite-modified raw materials can be used as the ceramic raw material. Cordierite-modified raw materials are raw materials that have been fired to become cordierite. The preferred chemical composition of the cordierite-modified raw material is: alumina (Al₂O₃) (including aluminum hydroxide components converted to alumina): 30–45% by mass, magnesium oxide (MgO): 11–17% by mass, and silicon dioxide (SiO₂): 42–57% by mass.
[0092] Examples of dispersion media include water or a mixture of water and organic solvents such as alcohols; however, water is particularly preferred.
[0093] As a pore-forming material, it is acceptable to use materials that form pores after firing; there are no particular limitations. Examples include: wheat flour, starch, foaming resin, water-absorbing resin, porous silica, carbon (e.g., graphite), ceramic cenospheres, polyethylene, polystyrene, polypropylene, nylon, polyester, acrylic, phenolic resins, etc. One type of pore-forming material can be used alone, or two or more can be used in combination. From the viewpoint of improving the porosity of the fired body, the content of the pore-forming material relative to 100 parts by mass of the ceramic raw material is preferably 0.5 parts by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more. From the viewpoint of ensuring the strength of the fired body, the content of the pore-forming material relative to 100 parts by mass of the ceramic raw material is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 4 parts by mass or less.
[0094] Examples of adhesives include organic adhesives such as methylcellulose, hydroxypropyl methylcellulose, hydroxyethyl cellulose, carboxymethyl cellulose, and polyvinyl alcohol. It is particularly preferred to use methylcellulose and hydroxypropyl methylcellulose together. Furthermore, from the viewpoint of improving the strength of the honeycomb molded body, the adhesive content relative to 100 parts by weight of the ceramic raw material is preferably 4 parts by weight or more, more preferably 5 parts by weight or more, and even more preferably 6 parts by weight or more. From the viewpoint of suppressing cracking due to abnormal heating during the firing process, the adhesive content relative to 100 parts by weight of the ceramic raw material is preferably 9 parts by weight or less, more preferably 8 parts by weight or less, and even more preferably 7 parts by weight or less. One type of adhesive can be used alone, or two or more types can be used in combination.
[0095] Dispersants can include ethylene glycol, dextrin, fatty acid soaps, polyether polyols, etc. A single dispersant can be used, or two or more can be used in combination. The preferred content of the dispersant relative to 100 parts by weight of the ceramic raw material is 0 to 2 parts by weight.
[0096] There is no particular limitation on the method for sealing the bottom surface of the columnar honeycomb molded body; well-known methods can be used. There are no particular limitations on the material of the sealing portion, but ceramic is preferred from the viewpoint of strength and heat resistance. As the ceramic, a ceramic material containing at least one of the following is preferred: cordierite, andalusite, zircon, zirconium phosphate, aluminum titanate, silicon carbide, silicon nitride, zirconium oxide, spinel, indigo, pseudosapphire, corundum, and titanium dioxide. Since this allows for a uniform expansion rate during firing and improved durability, it is more preferable that the sealing portion be composed of the same material as the partition walls of the honeycomb molded body.
[0097] After drying the honeycomb molded body, it is degreased and fired to produce a columnar honeycomb structure. The conditions for the drying, degreasing, and firing processes can be well-known conditions depending on the material composition of the honeycomb molded body. Although no special explanation is needed, examples of specific conditions are given below.
[0098] In the drying process, conventionally known drying methods such as hot air drying, microwave drying, dielectric drying, reduced pressure drying, vacuum drying, and freeze drying can be used. Among these, a drying method combining hot air drying and microwave drying or dielectric drying is preferred in terms of being able to dry the molded body quickly and uniformly.
[0099] When forming the sealing portion, it is preferable to dry the sealing portion after forming it on both bottom surfaces of the dried honeycomb molded body. The sealing portion is formed in a predetermined position in such a way that a plurality of first compartments extending from the bottom surface of the inlet side to the bottom surface of the outlet side, with the bottom surface of the inlet side open and the bottom surface of the outlet side having the sealing portion, and a plurality of second compartments extending from the bottom surface of the inlet side to the bottom surface of the outlet side, with the bottom surface of the inlet side having the sealing portion and the bottom surface of the outlet side open, are alternately arranged with porous partition walls.
[0100] Next, the degreasing process will be explained. The combustion temperature of the adhesive is around 200℃, and the combustion temperature of the pore-forming material is around 300-1000℃. Therefore, the degreasing process can be carried out by heating the honeycomb molded body to a range of around 200-1000℃. There is no particular limitation on the heating time, which is usually around 10-100 hours. The honeycomb molded body after the degreasing process is called the pre-burned body.
[0101] The firing process also depends on the material composition of the honeycomb molded body. For example, the pre-fired body can be heated to 1350–1600°C and held for 3–10 hours for the firing process. In this way, a columnar honeycomb structure is produced, which includes: a plurality of first compartments extending from the bottom surface of the inlet side to the bottom surface of the outlet side, with the bottom surface of the inlet side being open and the bottom surface of the outlet side having a sealing portion; and a plurality of second compartments extending from the bottom surface of the inlet side to the bottom surface of the outlet side, with the bottom surface of the inlet side having a sealing portion and the bottom surface of the outlet side being open. The plurality of first compartments and the plurality of second compartments are arranged alternately adjacent to each other, with porous partitions sandwiching them.
[0102] Next, a porous membrane is formed on the surface of the first compartment of the columnar honeycomb structure after the firing process. The following process is first performed: while spraying an aerosol containing ceramic particles toward the bottom surface of the inlet side, an attraction force is applied to the bottom surface of the outlet side to draw the sprayed aerosol from the bottom surface of the inlet side, so that the ceramic particles adhere to the surface of the first compartment.
[0103] At this point, the ceramic particles in the aerosol preferably have a sharp and fine particle size distribution. This sharp and fine particle size distribution results in a porous membrane with a homogeneous three-dimensional structure containing fine pores, making it easy to achieve high PN capture efficiency even with a thin membrane. Furthermore, by reducing the membrane thickness, low pressure loss can also be achieved. While it is difficult to accurately define the aforementioned homogeneous three-dimensional structure with fine pores, at least a portion of it exhibits low porosity.
[0104] Specifically, regarding ceramic particles in aerosols, when the median particle size in the cumulative particle size distribution based on volume diffraction scattering determined by laser diffraction scattering is set as D50 (unit: μm), 10% of the particle size is set as D10 (unit: μm), and 90% of the particle size is set as D90 (unit: μm), it is preferable to satisfy the relationships 0.1≤D50≤6.0 and 0.4≤D50 / (D90-D10).
[0105] The upper limit of the D50 of the ceramic particles is preferably 6.0 μm or less, more preferably 4.0 μm or less, and even more preferably 3.0 μm or less. The lower limit of the D50 of the ceramic particles is not specifically set, but from the viewpoint of ease of manufacture, it is usually 0.1 μm or more, preferably 0.5 μm or more, and more preferably 1.0 μm or more.
[0106] Sharp particle size distribution can be represented by D50 / (D90-D10). Using D50 / (D90-D10) as an indicator is particularly effective in representing the degree of agglomeration of ceramic particles. A D50 / (D50-D10) as specified in Patent Document 1 cannot express a sharp particle size distribution. A larger D50 / (D90-D10) indicates a sharp particle size distribution. Specifically, it is preferable to have 0.4 ≤ D50 / (D90-D10), more preferably 0.6 ≤ D50 / (D90-D10), further preferably 0.8 ≤ D50 / (D90-D10), and even more preferably 1.0 ≤ D50 / (D90-D10), for example, 0.4 ≤ D50 / (D90-D10) ≤ 1.5.
[0107] The ceramic particles used are those of the aforementioned ceramics constituting the porous membrane. Specifically, they may contain one or more ceramics selected from silicon carbide (SiC), cordierite, talc, mica, andalusite, ceramic fragments, aluminum titanate, alumina titanate, alumina, silicon nitride, silicon aluminum oxynitride ceramics, zirconium phosphate, zirconium oxide, titanium dioxide, and silicon dioxide (SiO2). For reasons of cost, availability, thermal shock resistance, and peel resistance, the ceramic particles preferably contain a total of 50% by mass or more of one or more of silicon carbide, cordierite, alumina, silicon dioxide, andalusite, more preferably 70% by mass or more, and even more preferably 90% by mass or more. For reasons of thermal shock resistance and peel resistance, the ceramic particles particularly preferably contain 50% by mass or more of silicon carbide, more preferably 70% by mass or more, and even more preferably 90% by mass or more.
[0108] Figure 5 The diagram schematically illustrates the configuration of a particle attachment device (500) suitable for performing the process of attaching ceramic particles to the surface of the first compartment of a columnar honeycomb structure (580). The particle attachment device (500) includes: an aerosol generator (510), a laser diffraction particle size distribution measuring device (520), a gas inlet pipe (530), a retainer (540), a differential pressure gauge (550), an exhaust pipe (560), and a blower (570).
[0109] The aerosol generator (510) is equipped with:
[0110] Cylinder (513), which is used to hold ceramic particles (512);
[0111] A piston or screw (514) is used to deliver ceramic particles (512) contained in the cylinder (513) from the cylinder outlet (513e);
[0112] A crushing chamber (515), which is connected to the cylinder outlet (513e), and includes a rotating body (516) for crushing ceramic particles (512) discharged from the cylinder outlet (513e); and
[0113] The gas flow path (517), which allows the medium gas to flow and is connected to the crushing chamber outlet (515e) along the way, is capable of spraying an aerosol containing the medium gas and ceramic particles (512) from the nozzle (511) installed at the front end.
[0114] The aerosol generator (510) is capable of spraying aerosol from the nozzle (511). Ceramic particles (512) with a predetermined particle size distribution are contained within the cylinder (513). The ceramic particles (512) contained within the cylinder (513) are extruded from the cylinder outlet (513e) via a piston or screw (514). The extrusion speed can be adjusted. The ceramic particles (512) discharged from the cylinder outlet (513e) enter the crushing chamber (515). The ceramic particles (512) introduced into the crushing chamber (515) are crushed by a rotating body (516), and simultaneously move within the crushing chamber (515) and are discharged from the crushing chamber outlet (515e). The rotating body (516) can be, for example, a rotating brush. The rotating body (516) can be driven by a motor and its rotation speed can be controlled.
[0115] Ceramic particles discharged from the crushing chamber outlet (515e) mix with the medium gas flowing through the gas flow path (517) to form an aerosol, which is then ejected from the nozzle (511). The nozzle (511) is preferably positioned and oriented to spray the aerosol toward the center of the inlet-side bottom surface of the columnar honeycomb structure (580) held in the retainer (540) in a direction perpendicular to the bottom surface of the inlet side.
[0116] The medium gas used is compressed air or other compressed gas with adjusted pressure, thereby enabling control of the injection flow rate from the nozzle (511). A laser diffraction particle size distribution measuring device (520) is provided in the gas flow path (517), which can measure the particle size distribution of ceramic particles in the aerosol discharged from the aerosol generator (510) in real time. Thus, it is possible to monitor whether ceramic particles with the desired particle size distribution are being supplied to the columnar honeycomb structure (580).
[0117] Fine ceramic particles have the property of easily agglomerating. However, since the broken ceramic particles are sprayed using the aerosol generator (510) according to this embodiment, ceramic particles with a target particle size distribution that can suppress agglomeration can adhere to the surface of the first compartment.
[0118] The aerosol ejected from the aerosol generator (510) is drawn through the gas inlet pipe (530) by the suction force from the blower (570) and then into the first compartment of the columnar honeycomb structure filter from the bottom surface of the inlet side of the columnar honeycomb structure held in the retainer (540). The ceramic particles in the aerosol drawn into the first compartment adhere to the surface of the first compartment.
[0119] Multiple vents (531) are provided on the wall of the gas inlet pipe (530) to draw in ambient air and other gases. This allows the flow rate of gas flowing into the gas inlet pipe (530) to be adjusted according to the suction force from the blower (570). For the purpose of preventing foreign matter from entering, filters can be provided in the vents (531).
[0120] An exhaust pipe (560) connected to a blower (570) is provided on the downstream side of the bottom surface of the outlet side of the columnar honeycomb structure (580). Therefore, if the aerosol from which ceramic particles have been removed is discharged from the bottom surface of the outlet side of the columnar honeycomb structure (580), it will be discharged through the blower (570) after passing through the exhaust pipe (560).
[0121] As the process of attaching ceramic particles to the surface of the first compartment continues, the pressure loss between the inlet and outlet bottom surfaces of the columnar honeycomb structure increases with the amount of attached ceramic particles. By pre-calculating the relationship between the amount of attached ceramic particles and the pressure loss, the endpoint of the process of attaching ceramic particles to the surface of the first compartment can be determined based on the pressure loss. Therefore, the particle attachment device (500) can be equipped with a differential pressure gauge (550) to measure the pressure loss between the inlet and outlet bottom surfaces of the columnar honeycomb structure (580), thereby determining the endpoint of the process based on the value of the differential pressure gauge.
[0122] When performing the process of attaching ceramic particles to the surface of the first compartment, since the ceramic particles are attached to the bottom surface of the inlet side of the columnar honeycomb structure (580), it is preferable to remove the ceramic particles by suction using a vacuum while using a tool such as a scraper to flatten the bottom surface of the inlet side.
[0123] Then, the columnar honeycomb structure with ceramic particles attached to the surface of the first compartment is heat-treated at a maximum temperature of 1000°C or higher for at least 1 hour, typically at a maximum temperature of 1100°C to 1400°C for 1 to 6 hours, thereby completing the columnar honeycomb structure filter. The heat treatment can be performed by placing the columnar honeycomb structure in, for example, a continuous firing furnace (e.g., a tunnel kiln) or a batch firing furnace (e.g., a shuttle kiln). For the sake of increasing production speed, it is preferable that the average heating rate during the heat treatment, from room temperature (25°C) to the maximum temperature, is 100°C / Hr or higher. Furthermore, for the sake of suppressing cracking, it is preferable that the average heating rate during the heat treatment, from room temperature (25°C) to the maximum temperature, is 200°C / Hr or lower. Additionally, for the sake of suppressing cracking and reducing the burden on the kiln material, it is preferable that the average cooling rate during the heat treatment, from the maximum temperature to room temperature (25°C), is 200°C / Hr or lower. Through heat treatment, ceramic particles are bonded together and sintered into the partition wall of the first compartment, forming a porous film on the surface of the first compartment. If the heat treatment is carried out under oxygen-containing conditions such as air, a surface oxide film is formed on the surface of the ceramic particles, promoting the bonding of the ceramic particles together. Thus, a porous film that is not easily peeled off is obtained.
[0124] The average thickness T (in μm) of the porous membrane formed on the surface of the first compartment through heat treatment preferably satisfies the relationship 4 × D50 ≤ T ≤ 20 × D50 with respect to the D50 (in μm) of the ceramic particles. This relationship indicates that a smaller average membrane thickness T is more desirable when D50 is small, and a larger average membrane thickness T is more desirable when D50 is large. The reason is that the smaller D50 is, the smaller the waste gas flow path of the porous membrane, thereby improving the collection efficiency.
[0125] Example
[0126] The following examples illustrate embodiments for a better understanding of the invention and its advantages; however, the invention is not limited to these examples.
[0127] (1) Manufacturing of columnar honeycomb structure filter
[0128] To prepare clay, 3 parts by mass of pore-forming material, 55 parts by mass of dispersion medium, 6 parts by mass of organic binder, and 1 part by mass of dispersant are added to 100 parts by mass of cordierite petrochemical raw material. The mixture is then kneaded and mixed. The cordierite petrochemical raw material used includes alumina, aluminum hydroxide, kaolin, talc, and silica. Water is used as the dispersion medium, a water-absorbing polymer is used as the pore-forming material, hydroxypropyl methylcellulose is used as the organic binder, and fatty acid soap is used as the dispersant.
[0129] The clay is placed in an extrusion molding machine and extruded using a die of a specified shape to obtain a cylindrical honeycomb molded body. After dielectric drying and hot air drying, the two bottom surfaces of the obtained honeycomb molded body are cut off to specified dimensions to obtain a dried honeycomb body.
[0130] The honeycomb dried body was sealed with cordierite using alternating adjacent first and second compartments. Then, it was degreased by heating at about 200°C in an atmospheric atmosphere. In addition, it was fired at 1420°C for 5 hours in an atmospheric atmosphere to obtain a columnar honeycomb structure.
[0131] The specifications of the columnar honeycomb structure are as follows.
[0132] Overall shape: Cylindrical, 132mm in diameter × 120mm in height
[0133] The compartment shape in a cross-section perpendicular to the flow path direction of the compartment: square
[0134] Compartment density (number of compartments per unit cross-sectional area): 200 cpsi
[0135] Average pore size: 9μm
[0136] Porosity: 55%
[0137] Partition wall thickness: 8 mil (200 μm) (nominal value based on die specifications)
[0138] For the columnar honeycomb structure fabricated above, using Figure 5 The particle attachment device shown allows ceramic particles to adhere to the surface of the first compartment. The operating conditions of the particle attachment device are as follows.
[0139] • Aerosol generator: PALAS RBG2000
[0140] • Ceramic particles contained in the cylinder: as recorded in Table 1 (in the table, "main raw material" means that it consists of more than 90% by mass of the substances shown).
[0141] (The particle size distribution of the ceramic particles contained in the cylinder was changed according to the test number.)
[0142] Medium gas: dry air
[0143] • Surrounding gas: Atmosphere
[0144] • Average flow rate of aerosol flowing within the columnar honeycomb structure: 3000 L / min
[0145] • Laser diffraction particle size distribution measuring device: Incitec Spray manufactured by MALVERN
[0146] In the operation of the particle attachment device, a laser diffraction particle size distribution measuring device was used to measure the particle size distribution of ceramic particles discharged from the aerosol, and D50 and D50 / (D90-D10) were measured. The results are shown in Table 1. These results confirm that in both the embodiment and the comparative example, the particle size distribution was substantially the same as that of the ceramic particles contained in the cylinder, and no agglomeration occurred.
[0147] While using a scraper to flatten the bottom surface of the columnar honeycomb structure with attached ceramic particles, the ceramic particles attached to the bottom surface of the inlet side are removed using a vacuum. Then, the columnar honeycomb structure is placed in an intermittent electric furnace and heated in an atmospheric atmosphere at a maximum temperature of 1200°C for 2 hours, thereby forming a porous membrane on the surface of the first compartment, resulting in a columnar honeycomb filter. During the heating oxidation treatment, in any test example, the average heating rate from room temperature (25°C) to the maximum temperature was set to 100°C / Hr, and the average cooling rate from the maximum temperature to room temperature (25°C) was set to 100°C / Hr. It should be noted that only a quantity of the columnar honeycomb filter was produced in order to perform the following characteristic evaluation.
[0148] (2) Characteristic Evaluation
[0149] [Membrane weight]
[0150] The weight of the porous membrane for each columnar honeycomb structure filter obtained using the above manufacturing method was determined. Specifically, the membrane weight was obtained by subtracting the weight of the columnar honeycomb structure before the ceramic particles were attached from the weight of the columnar honeycomb structure filter. The results are shown in Table 1.
[0151] [Average film thickness]
[0152] Using the aforementioned method, the average membrane thickness of the porous membranes of each columnar honeycomb structure filter obtained by the above manufacturing method was measured. A Keyence VR-3200 3D shape measuring machine was used for the measurement. The results are shown in Table 1.
[0153] [Membrane porosity]
[0154] The porosity of the porous membrane was measured using the aforementioned method. The apparatus used for the measurement included a FE-SEM (model: ULTRA55 (manufactured by ZEISS)) and the image analysis software HALCON. The results are shown in Table 1. An illustrative FE-SEM image of the porous membrane from Example 2 is shown below. Figure 8 The gray areas represent the membrane material, and the black areas represent the voids.
[0155] The “capture efficiency (%)” and “pressure loss” of each columnar honeycomb structure filter obtained by the above manufacturing method are measured according to the following steps.
[0156] [Capture Efficiency (%)]
[0157] A columnar honeycomb filter was connected to the outlet side of the exhaust manifold of a 1.2L direct-injection gasoline engine vehicle. The number of soot particles in the exhaust gas exiting from the outlet of the columnar honeycomb filter was measured using the PN measurement method. Regarding driving modes, a worst-case scenario simulation of RDE driving (RTS95) was implemented. The cumulative number of soot particles emitted after driving in this mode was set as the soot particle count of the exhaust gas purification device, and the collection efficiency (%) was calculated based on this soot particle count. The results are shown in Table 1.
[0158] [Pressure Loss]
[0159] The exhaust gas from the 1.2L direct-injection gasoline engine is heated to 700℃ and sprayed at 600m. 3 A flow rate of / h was introduced, and the pressures at the inlet and outlet sides of the columnar honeycomb filter were measured. The pressure difference between the inlet and outlet sides was then calculated, from which the pressure loss (kPa) of the honeycomb filter was determined. The results are shown in Table 1.
[0160] Table 1
[0161]
[0162] (3) Investigation
[0163] Figure 6 The relationship between the average membrane thickness and porosity of the porous membranes in the embodiments and comparative examples is shown. Additionally, Figure 7 The table shows the relationship between the median particle size (D50) of ceramic particles in the aerosols of the examples and comparative examples and the average thickness of the porous membranes. (Table 1 and...) Figure 6 It can be seen that porous membranes with average film thickness T and porosity P meeting the specified conditions can simultaneously achieve high PN capture efficiency and low pressure loss. Furthermore, from Table 1 and... Figure 7 It can be seen that when D50, D50 / (D90-D10), and average film thickness T meet the specified conditions, a porous membrane that can simultaneously achieve high PN capture efficiency and low pressure loss can be obtained.
Claims
1. A method for manufacturing a columnar honeycomb structure filter, comprising the following steps: A process for preparing a columnar honeycomb structure, the columnar honeycomb structure comprising: a plurality of first compartments extending from an inlet-side bottom surface to an outlet-side bottom surface, the inlet-side bottom surface being open and the outlet-side bottom surface having a sealing portion; and a plurality of second compartments extending from an inlet-side bottom surface to an outlet-side bottom surface, the inlet-side bottom surface having a sealing portion and the outlet-side bottom surface being open, the plurality of first compartments and the plurality of second compartments being alternately arranged adjacent to each other, sandwiched by porous partition walls; and The process involves simultaneously spraying an aerosol containing ceramic particles from a direction perpendicular to the bottom surface of the inlet side towards the bottom surface of the outlet side, and simultaneously applying an attractive force to the bottom surface of the outlet side to draw the sprayed aerosol from the bottom surface of the inlet side, causing the ceramic particles to adhere to the surface of the first compartment. The aerosol spraying is carried out using an aerosol generator, which includes: a gas flow path for supplying pressurized medium gas, a supply port disposed in the gas flow path and capable of drawing ceramic particles from the outer periphery of the gas flow path into the gas flow path, and a nozzle installed at the front end of the gas flow path and capable of spraying aerosol. Regarding ceramic particles in aerosols, when the median particle size in the cumulative particle size distribution based on volume diffraction scattering determined by laser diffraction scattering is set as D50, the 10% particle size is set as D10, and the 90% particle size is set as D90, the following relationships are satisfied: 0.1 ≤ D50 ≤ 6.0 and 0.4 ≤ D50 / (D90 - D10). The units of D50, D10, and D90 are all μm.
2. The method for manufacturing the columnar honeycomb structure filter according to claim 1, characterized in that, The ceramic particles contain a total of more than 50% by mass of one or more of silicon carbide, cordierite, alumina, silica, andalusite, and aluminum titanate.
3. The method for manufacturing the columnar honeycomb structure filter according to claim 1 or 2, characterized in that, The aerosol generator also features: The cylinder body contains ceramic particles; A piston or screw used to expel ceramic particles contained within the cylinder from the cylinder outlet; and The crushing chamber is connected to the cylinder outlet and has a rotating body for crushing ceramic particles sent from the cylinder outlet, and a crushing chamber outlet connected to the supply port.
4. The method for manufacturing the columnar honeycomb structure filter according to claim 1 or 2, characterized in that, In the process of attaching ceramic particles to the surface of the first compartment, aerosol is sprayed from the nozzle toward the center of the bottom surface of the inlet side of the columnar honeycomb structure in a direction perpendicular to the bottom surface of the inlet side.
5. The method for manufacturing a columnar honeycomb structure filter according to claim 1 or 2, characterized in that, A laser diffraction particle size distribution measuring device is installed in the gas flow path. During the process of attaching ceramic particles to the surface of the first compartment, the particle size distribution of ceramic particles in the aerosol discharged from the aerosol generator is measured in real time.
6. The method for manufacturing a columnar honeycomb structure filter according to claim 1 or 2, characterized in that, In the process of attaching ceramic particles to the surface of the first compartment, the aerosol sprayed from the aerosol generator is drawn in from the bottom surface of the inlet side after passing through the gas inlet pipe.
7. The method for manufacturing the columnar honeycomb structure filter according to claim 6, characterized in that, Multiple vent holes are provided on the wall of the gas inlet pipe.
8. The method for manufacturing a columnar honeycomb structure filter according to claim 1 or 2, characterized in that, The endpoint of the process of attaching ceramic particles to the surface of the first compartment is determined based on the value of a differential pressure gauge installed to measure the pressure loss between the bottom surface of the inlet side and the bottom surface of the outlet side of the columnar honeycomb structure.
Citation Information
Patent Citations
Double-layered structural honeycomb filter and its production
JP2000202220A
Honeycomb filter for dust collection and its production
JP2001079321A
Honeycomb body and particulate filter comprising a honeycomb body
WO2019089806A1
Honeycomb filter production apparatus
CN102188857A
Ceramic honeycomb structure
CN107427823A